The implications of management styles on the level of occupational stress in the library setting - Nierras, Marvic C.; Santos, Herminia H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
This study focused on examining the relationship between occupational stress and management styles within unit libraries in U.P. Diliman. In order to accomplish this, it was necessary to determine the following: 1) the management styles being employed by the administrators of unit libraries, 2) the level of occupational stress experienced by the staff of these unit libraries and 3) the differences in the level of occupational stress experienced by staff of libraries whose administrators employ different management styles.
The proponent used a survey questionnaire that aims to find out 1) the organizational conditions that are considered by the library staff as stressors, 2) the level of occupational stress experienced by the library staff and 3) the management styles employed by library administrators as perceived by the library staff. This questionnaire was administered to 19 unit libraries in UP Diliman. The questionnaires were returned, 3 were then selected from each library, yielding a total of 57 responses.
Results revealed that System 3 (consultative) is the most commonly employed management style, followed by System 2 (benevolent-authoritative) and System 4 (participative-group) being the least commonly used. None employed a System 1 (exploitative-authoritative) management style.
There were library staff who experienced `strong' to `very strong' levels of occupational stress and they identified four common organizational stressors, namely: 1) superiors' lack of support for job-related problems, 2) non-participation in decisions that affect their work, 3) lack of consultation and communication and 4) managerial feedback which focuses on mistakes.
The management style of library administrators does affect the level of occupational stress experienced by their staff, which in turn varies per management style. Moreover, an issue of concern here is the fact that the organizational stressors identified by the library staff point out to the interpersonal aspects of management style - an aspect that a participative management style gives emphasis to. This supports the result of lower levels of stress for management styles belonging to Systems 2 to 4.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic librarians; Academic libraries -- Administration; Job stress